PENGARUH STANDAR AKUNTANSI PEMERINTAH, SISTEM INFORMASI AKUNTANSI DAN KUALITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS KINERJA PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG PROVINSI LAMPUNG - Anwar, Amelia; Juryani, Septi (TECHNOBIZ : International Journal of Business, 2023)
The purpose of this study is to determine how much influence government accounting standards, accounting information systems, and the quality of financial statements have on performance accountability at the Public Works and Spatial Planning Office of Lampung Province. In this study using a quantitative descriptive approach where the data processing is carried out statistically. The number of samples taken was 44 respondents using the Non probability sampling method. The source of data in this study is primary data obtained using questionnaires which are then processed with multiple linear analysis tests using SPSS version 21. The results of this study show that Government Accounting Standards, Accounting Information Systems and Financial Statement Quality have a positive and significant effect simultaneously on the Performance Accountability of the Public Works and Spatial Planning Office of Lampung Province. Keywords: government accounting standards, accounting information systems, quality of financial statements, performance accountability